DETECTION OF INDUCIBLE CLINDAMYCIN RESISTANCE AMONG COAGULASE NEGATIVE STAPHYLOCOCCUS ISOLATED FROM HEALTHY POPULATION - P, Deeksheeta; Gopinath,; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Clindamycin is an attractive agent for empirical therapy for various infections because of its excellent pharmacokinetic and pharmacodynamic properties. Clinical failures of clindamycin therapy for treatment of MRSA infections have been documented for strains that were clindamycin sensitive but erythromycin resistant. The failures were due to inducible resistance to clindamycin. A total of 20 normal flora isolates of Coagulase-negative staphylococci (CoNS) were subjected to an antibiotic sensitivity pattern followed by an inducible clindamycin resistance test. 20% were found to be D test-positive strains. The D-test is a simple & reliable method to detect inducible & constitutive clindamycin resistance in routine clinical diagnosis settings.